Success and failure of African exporters - Cadot, Olivier; Iacovone, Leonardo; Pierola, Martha Denisse; Rauch, Ferdinand (Journal of development economics, 2013)
Using a new dataset with transaction-level export data from four African countries (Malawi, Mali, Senegal and Tanzania), this paper explores the determinants of success upon entry into export markets, defined as survival beyond the first year at the firm-product-destination level. We find that the probability of success rises with the number of same-country firms exporting the same product to the same destination, suggesting the existence of cross-firm externalities. We explore several conjectures on the determinants of these externalities and provide evidence suggestive of information spillovers, possibly mediated through the banking system.